A Philosophical and Historical Analysis on Peculiarities of the Conception of Law in Russia in the Second Half of 19th – Early 20th Centuries - Khrapov, Sergey A.; Saveleva, Elena V.; Haritonova, Anna N.; Goverdovskaya, Tatyana V.; Kripakova, Dina R. (Journal of History Culture and Art Research, 2018)
Minds of many scientists are occupied with the issue of a need to formulate new theoretical approaches to defining the essence of law in the environment of extensive and dynamic changes in the conception of law. Scientific literature contains different handlings of the legal theories on the issue of the essence of law, belonging both to the past and present. The authors propose to implement universal logical principles of scientific theorization, developed in science studies, in the modern theory of law to create a human-centered scientific legal theory that is sought after by jurists.